2014
DOI: 10.1093/mtp/miu030
|View full text |Cite
|
Sign up to set email alerts
|

Music Therapy Ethics "2.0": Preventing User Error in Technology

Abstract: The use of technology in music therapy, specifically through social media, computer-mediated music therapy, and advertising, is rapidly evolving. This has unique implications for ethical practice, particularly as technology usage expands and evolves. This article explores the benefits and risks of technology, along with guidelines that promote ethical thinking and habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
1
3
0
2
Order By: Relevance
“…Just as music therapists offer assistance in coping with change, they must also demonstrate their own ability to cope with change. We concur with previous literature that telehealth will likely be embedded in the overall practice of healthcare and that healthcare workers must be proficient in using the medium (Bates, 2014;Hagland, 2020). Not only is it important to acknowledge a new standard of competence, but it is also worth discussing potential improvements to the capabilities that telehealth sessions can offer and the implications for future research.…”
Section: Personal Reflections and Improvementssupporting
confidence: 90%
“…Just as music therapists offer assistance in coping with change, they must also demonstrate their own ability to cope with change. We concur with previous literature that telehealth will likely be embedded in the overall practice of healthcare and that healthcare workers must be proficient in using the medium (Bates, 2014;Hagland, 2020). Not only is it important to acknowledge a new standard of competence, but it is also worth discussing potential improvements to the capabilities that telehealth sessions can offer and the implications for future research.…”
Section: Personal Reflections and Improvementssupporting
confidence: 90%
“…Through the work being done, it is becoming increasingly evident that creative arts therapies telehealth can yield similarly beneficial effects to in-person services by meeting patients in familiar environments such as their homes and communities. This ameliorates the need for travel to a medical centre and provides a degree of autonomy and control of the delivery, environment, and participation level in treatment [37]. This autonomy can promote adherence to treatment plans, enabling patients to integrate telehealth sessions into their daily routines and having the independence to seek treatment in their chosen environments.…”
Section: Discussionmentioning
confidence: 99%
“…MT scholars reported that MT can be delivered to older adults via telehealth (78, 79). Although MTT was already in existence (80,81), it was popularized out of necessity during the COVID-19 pandemic (82). Various MT authors have described MTT as a potential service delivery model (78,79).…”
Section: Rationale For Protocolized Music Tele-therapymentioning
confidence: 99%